(untitled) (Pesquisa Odontológica Brasileira, 2001)
In the present study, the authors evaluated the Tanaka-Johnston method of prediction, with the objective of verifying its effectiveness for the right and left sides, for both genders and for the white, light mulatto, medium mulatto, dark mulatto and black races in the city of Salvador, Bahia. The mesiodistal diameter of the inferior permanent incisors, canines and premolars that had already erupted was measured with the aid of a digital caliper rule in the oral cavity of 98 individuals (45 males and 53 females), aging from 13 to 29 years. The results obtained with the application of the Tanaka-Johnston formulas were compared with the real values through statistical tests. After the analysis of the results, it was observed that the correlation between the estimated values and the real values was greater for females than it was for males. As to race, the coefficients of correlation were satisfactory. They were greater in the superior arch for the dark mulatto race (0.67), and in the inferior arch for the light mulatto race (0.74). Considering the sides, the findings revealed a greater coefficient of correlation for the inferior arch on the left side (0.61). It was concluded that the Tanaka-Johnston method, in spite of originating from a sample of European descendants, is indicated for the prediction of the mesiodistal diameter of canines and premolars in the different races evaluated in this research. The effectiveness of the referred method was also checked for both genders and sides in the studied sample.